KING AND SINGING BOBURMIRZO - IMPORTANT IMAGE OF THE WORLD ORIENTALS - Baymanov Habibullo Abdullaevich (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the role of Babur’s creations in world literature and its study by foreign literary critics. In particular, his creations on cultural linguistics, comparative literary criticism, contrastive linguistics and translation studies serve as an important source in a wide range of scientific fields.